THE FOUNDATION OF THE MODERN SERBIAN STATE IN THE FIRST SERBIAN UPRISING 1804 - 1813 (Heritage, 2021)
Already in the first year of the First Serbian uprising, there was a need to establish certain authorities in the area liberated from the Turks. For that purpose, the Governing Council (Praviteljstvujšći sovjet) was established, it would later grow into the Government and all other executive bodies in the local self-government. Local assemblies and the National Assembly were established as the highest legislative body of the First Serbian uprising. The foundations were laid for the courts, as the third branch of government during the uprising. At that time, the foundations were laid for the Serbian army, which had its own uniform and oath. The police and intelligence services were formed, as well as the budget. All these branches of government developed and improved during the 19th and 20th centuries. In the First Serbian uprising, the foundations of the modern Serbian state were laid.
Keywords: Karađorđe, uprising, foundation, law, court, army